Factors Affecting the Underpricing of Shares of Companies that Conduct Initial Public Offerings with the Auditor's Reputation as a Moderator - Ni Wayan Trisna Purnama Dewi Dewi; Henny Triyana Hasibuan; Gerianta Wirawan Yasa (Journal of Social Research, 2025)
Underpricing remains a prevalent phenomenon in initial public offerings (IPOs) in Indonesia. Despite global and national economic uncertainties, statistical data from the Indonesia Stock Exchange (IDX) reveal significant growth in both the investor base and the number of IPOs during the 2020–2024 period. This study aims to identify the determinants of underpricing for companies that conducted IPOs on the IDX between 2020 and 2024, with auditor reputation serving as a moderating variable. This quantitative research employs Signaling Theory to analyze the informational cues available during and after the IPO process. The independent variables examined in relation to underpricing include Return on Assets (ROA), Debt to Equity Ratio (DER), Earnings Per Share (EPS), and Firm Size, with Auditor Reputation incorporated as a moderating variable to assess its influence on the relationships. The study’s population consists of firms that completed IPOs on the IDX from 2020 to 2024. A purposive sampling technique was utilized, resulting in a final sample of 177 companies. Data analysis was conducted using SPSS software, specifically applying the Moderated Regression Analysis method. The findings offer empirical evidence that DER has a significant effect on underpricing. In contrast, ROA, EPS, and Firm Size do not exhibit a statistically significant impact on underpricing. Furthermore, statistical tests indicate that Auditor Reputation does not enhance the moderating effect of ROA, DER, EPS, or Firm Size on underpricing.